Silanes and Allylsilanes as Possible Precursors for Transition Metal-Stabilized Silylium Ions - Ruffolo, Raffaele (My University, 1997)
Extended Huckel molecular orbital calculations on silicon cations [HC≅C-SI(CH₃)₂Co₂(CO)₆]⁺ reveal that the favored geometry for this silylium ion requires the SiH₂ group to lean towards a Co(CO)₃ vertex. This parallels the known behavior of carbocations with metal cluster vertices whereby the electron-deficient center is stabilized by a direct interaction with an organometallic fragment. These calculations also show that replacement of Co(CO)₃ vertices by isolobal CpMo(CO)₂ groups noticeably enhances the stabilization of the silylium moiety. The most successful approach for the synthesis of silylium ions reported to date has been the removal of hybride from a suitable silane precursor. In the attempt to generate a metal-stabilized silylium ion the silane, (CH₃)₃Si-C≅C-Si(C₆H₅)₂H[Mo₂(CO)₄Cp₂], was treated with triphenylmethyl tetrafluoroborate; however, the cluster compound was recovered unchanged. It is apparent from the X-ray structure that the dimetallic cluster and the two phenyl groups inhibit the approach of the trityl for reaction with the Si-H group. The next strategy used in the study involved construction of a tetracoordinate silicon with an alkynyl, two alkyl substituents and a fourth group possessing a reactive site, outside the steric sphere, capable of being removed when treated with the appropriate reagent. In our studies, protonation of an alkynyl-allylsilane (free, or metal-complexed alkyne) with either HBF₄ or triflic acid readily occurs with elimination of propene and formation of the corresponding silyl fluoride or triflate. A competition reaction between free and metal-complexed aklynyl-allylsilanes with a limiting amount of acid showed no discrimination between free alkynes or their metal complexed analogues. The study of precursor compounds which contain both a carbocation site (i.e., alcohol or isopropenyl) and an allylsilane yielded initially the metal stabilized carbocation which subsequently underwent allyl transfer with concomitant formation of a fluorosilane. In contrast, replacement of a a cobalt tricarbonyl vertex by Fe(CO)₃ fragment gave, upon treatment with HBF₄, the corresponding fluorosilane that was characterized by X-ray crystallography.
Keywords: Chemistry; Chemistry